Co-producing Community with Disabled Researchers and Citizens: the Challenges and Potential for Successful Collaboration - Dix, Geof; Hollinrake, Sue; Spencer, Sara (Participatory Social Work: Research, Practice, Education, 2019)
The chapter discusses the development of a collaborative research project, involving a service user-led Coalition of Disabled People, a local authority and a local university. The collaboration was set up to inform the Coalition’s strategic planning and to raise awareness of disability issues locally, mapping assets and resources for/of disabled people, as well as needs and resource gaps. The initial pilot of this “listening project” is critiqued here. It adopted an inclusive approach to the differing roles and competences within the project co-ordinating team, whose members worked together to recruit and train disabled researchers and engage a small sample of participants. The project drew on ideas from emancipatory disability research to inform its approach. The discussion evaluates the benefits and challenges of a collaborative approach to data collection, analysis and dissemination of findings, to achieve meaningful change locally, critically reflecting on praxis and the project’s effectiveness.